(untitled) (Bangladesh Journal of Medical Science, 2013)
Total of 300 TB patients sample were collected from NIDCH (Indoor and Outdoor) for six months period where three different specimens (sputum, pus, BAL) were collected among different age group (male and female). In sputum sample, percentage of identified samples in Auramine-O stain was 41% whereas in Z-N stain 32%; in pus sample, Auramine stain is 22% and Z-N stain 15%; In BAL sample, Auramine stain is 12% and Z-N stain is 10%. Therefore, out of 300 samples, 25% of positive samples were identified by Auramine-O staining whereas 19% of positive samples were identified by Z-N stain. In all the cases Auramine-O is found better for identification of TB than Z-N. In sputum, male positive 10%, female positive 3.66%; in pus sample, male positive 5% and female positive 2.33%; in BAL sample, male positive 3% and female positive 1%. Age group of 26 to 45 years were found high rate of TB in male patients. Bangladesh Journal of Medical Science Vol. 12 No. 03 July 13 Page 315-319 DOI: http://dx.doi.org/10.3329/bjms.v12i3.11104